2017
DOI: 10.1136/openhrt-2017-000629
|View full text |Cite
|
Sign up to set email alerts
|

Mortality and oral anticoagulants in the Food and Drug Administration Adverse Event Reporting System

Abstract: ObjectiveThe comparative crude death rates (CDR) among non-vitamin K antagonist oral anticoagulants (NOACs) are unknown. Further, whether NOACs improve survival when compared with warfarin is also unclear. We compared CDR co-reported for four NOACs combined or separately versus warfarin within the US Food and Drug Administration (FDA) Adverse Event Reporting System (FAERS) database.MethodsWe selected CDR from the FAERS database linked to four NOACs and warfarin. The primary endpoints were differences in propor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 12 publications
1
10
0
1
Order By: Relevance
“…Our analysis of over 40 000 oral anticoagulant–related adverse event cases reported to the FDA found rivaroxaban had a numerically higher rate of the included adverse events, and a significantly higher proportional reporting ratio for breakthrough venous thromboembolism. Our findings are parallel to prior work using FAERS to assess DOAC safety some of which found disproportionate safety reports with rivaroxaban . Our findings also parallel multiple large observational studies that comparatively evaluate DOACs, several of which have found increased thromboembolic events and bleeding with rivaroxaban as compared with other oral anticoagulants .…”
Section: Discussionsupporting
confidence: 84%
“…Our analysis of over 40 000 oral anticoagulant–related adverse event cases reported to the FDA found rivaroxaban had a numerically higher rate of the included adverse events, and a significantly higher proportional reporting ratio for breakthrough venous thromboembolism. Our findings are parallel to prior work using FAERS to assess DOAC safety some of which found disproportionate safety reports with rivaroxaban . Our findings also parallel multiple large observational studies that comparatively evaluate DOACs, several of which have found increased thromboembolic events and bleeding with rivaroxaban as compared with other oral anticoagulants .…”
Section: Discussionsupporting
confidence: 84%
“…However, the reduction in mortality risk as a secondary endpoint in clinical trials was not significant for NOACs [7][8][9], with the exception of edoxaban [14]. While some observational studies suggest a reduced risk of all-cause mortality among NOAC users, as compared to VKAs [15][16][17][18][19][20][21][22], the evidence is conflicting. Importantly, many observational studies use an ever versus never exposure definition that does not permit switching between medications.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, in many of these studies, they were unable to statistically adjust for lifestyle factors that may influence mortality, such as body mass index and smoking status. Finally, these studies did not exclude prior aspirin use in AF [15][16][17][18][19][20][21][22][23][24][25][26]. Although low-dose aspirin has been removed from the treatment guidelines for AF, use is still observed.…”
Section: Introductionmentioning
confidence: 99%
“…The Japanese Adverse Drug Event Report (JADER) and the FDA Adverse Event Reporting System (FAERS) include several million spontaneous reports of drug-associated adverse events from healthcare professionals and pharmaceutical companies [6]. In Japan, JADER was established by the Pharmaceuticals and Medical Devices Agency (PMDA) [7].…”
Section: Methodsmentioning
confidence: 99%